2000
DOI: 10.1071/bt99013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium chloride on seed germination and growth of two Chinese desert shrubs, Haloxylon ammodendron and H. persicum (Chenopodiaceae)

Abstract: The effects of sodium chloride (NaCl), polyethylene glycol-6000, temperature and light on germination and the effects of NaCl on growth were investigated in two Chinese desert shrubs, Haloxylon ammodendron (C.A.Mey.) Bunge and H. persicum Bunge ex Boiss. et Buhse. Both species occur in non-saline sand dunes; H. ammodendron also occurs in saline land, although it is not dominant there. Percentage germination of H. ammodendron and H. persicum in -3.0 MPa (667 mmol kg -1 ) NaCl was 91 and 64%, respectively. Hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 24 publications
3
77
1
Order By: Relevance
“…In different regions, due to different environmental conditions, seed traits display genetic variation in adapting to the environment (Rehfeldt 1993); thus, seeds of different provenances display different morphological and physiological characteristics of (Johnsen and Seiler 1996). Recent research on H. ammodendron has mainly focused on its ecological functions, droughttolerance mechanisms, physiological characteristics and biochemical characteristics (Huang et al 2003;Jiang et al 2004;Li et al 2007;Song et al 2005Song et al , 2006Su et al 2004Su et al , 2007Sun et al 2002;Tobe et al 2000Tobe et al , 2005Ungar 1991;Wang et al 2005;Wei et al 2007;Xu et al 2006). Studies of H. ammodendron provenances in China have been rare.…”
Section: Introductionmentioning
confidence: 94%
“…In different regions, due to different environmental conditions, seed traits display genetic variation in adapting to the environment (Rehfeldt 1993); thus, seeds of different provenances display different morphological and physiological characteristics of (Johnsen and Seiler 1996). Recent research on H. ammodendron has mainly focused on its ecological functions, droughttolerance mechanisms, physiological characteristics and biochemical characteristics (Huang et al 2003;Jiang et al 2004;Li et al 2007;Song et al 2005Song et al , 2006Su et al 2004Su et al , 2007Sun et al 2002;Tobe et al 2000Tobe et al , 2005Ungar 1991;Wang et al 2005;Wei et al 2007;Xu et al 2006). Studies of H. ammodendron provenances in China have been rare.…”
Section: Introductionmentioning
confidence: 94%
“…In related genera, lower temperatures promote seed germination in Haloxylon recurvum, while high temperatures delay seed germination significantly at various NaCl treatments (Khan and Ungar, 1996). Seed germination of Haloxylon ammodendron is relatively high at 10-20°C, while it decreases severely when temperatures are over 20°C (Huang et al, 2003;Tobe et al, 2000), indicating that seeds of these Haloxylon species may germinate in early spring, rather than in late spring or summer. Halostachys caspica, H. strobilaceum and K. foliatum are dominant halophytic species with high salt resistance which occur occasionally in association with H. ammodendron in saline soils in Xinjiang, China.…”
Section: Introductionmentioning
confidence: 94%
“…In the case of H. ammodendron, low soil salinity in the dune may hamper seedling survival. A study conducted by [32] a hydroponic culture of H. ammodendron at approximately three months was subjected to NaCl solution of 0, 200, 400 and 600 mmol/kg. The study found that the survival was highest at 400 mmol/kg of NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by [32] carried out an experiment to measure the percentage of germination and concluded that the ideal seed germination temperature was around 20°C and that temperature increases lessen the percentage of germination. In this experiment, however, maximum germination was recorded at 25°C.…”
Section: Literature Reviewmentioning
confidence: 99%